2021
DOI: 10.1002/imhj.21965
|View full text |Cite
|
Sign up to set email alerts
|

Fathers’ experiences of fetal attachment: A qualitative study

Abstract: Paternal‐fetal attachment (PFA) is associated with the degree of emotional support offered by fathers during pregnancy and has implications for the safety and quality of a mother's labor and postnatal experiences. This study explored fathers’ experiences of PFA including their understanding of the phenomenon and its manifestation. Data were collected through interviews with 10 fathers‐to‐be and analysis followed an interpretative phenomenological approach. Four themes emerged from the data: trigger moment; awa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
1
4
0
2
Order By: Relevance
“…Whilst higher scores are typically considered to reflect a more developed bond, no optimal value has been reported [ 23 ]. A positive correlation between bonding and GA has been previously observed [ 72 ], and supports the theory of key ‘trigger moments’ throughout pregnancy to intensify the bond [ 19 ]. However, this implies that bonding is a linear process, which may not be reflective of all parents’ experiences.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Whilst higher scores are typically considered to reflect a more developed bond, no optimal value has been reported [ 23 ]. A positive correlation between bonding and GA has been previously observed [ 72 ], and supports the theory of key ‘trigger moments’ throughout pregnancy to intensify the bond [ 19 ]. However, this implies that bonding is a linear process, which may not be reflective of all parents’ experiences.…”
Section: Discussionsupporting
confidence: 81%
“…After scanning, some parents remarked how the pregnancy felt more ‘real’ and expressed excitement imagining the baby in their lives. This may highlight scans as a’trigger moment’ where the bond is initiated or intensified [ 19 ], and parents are prompted to engage with their new caregiving role [ 51 ]. For some, the scan was an opportunity to learn the fetal sex, which further contributed to feelings of closeness to the baby and excitement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, both maternity and paternity are complex processes that, in many ways, are still influenced by parents’ respective cultures [ 5 ]. Various studies have shown that, like mothers, fathers also develop affective bonds with the fetus during the course of a pregnancy [ 6 , 7 ]. These bonds are cultivated by the idea of the unborn child already being part of the family and known by both parents [ 6 ].…”
Section: Introductionmentioning
confidence: 99%